Strukturierte ambulante Patientenversorgung im Facharztvertrag Orthopädie: die Erfahrungen der Patienten als Qualitätskriterium - Klingenberg, Anja; Kaufmann-Kolle, Petra; Wensing, Michel; Götz, Katja; Jahed, Jeanette; Lembeck, Burkhard; Flechtenmacher, Johannes; Szecsenyi, Joachim (Zeitschrift für Orthopädie und Unfallchirurgie, 2017)
In 2015 a survey was conducted in Baden-Württemberg (Germany) among patients treated by orthopaedic specialists participating in a medical specialists' contract between doctors and statutory health insurance funds, in accordance with § 73c of the German Social Code, Book V (SGB V). This contract aims to improve orthopaedic care by structured cooperation between orthopaedic specialists and general practitioners, who are the central coordinators of care, and refer patients to a specialist if necessary. The program is intended to achieve patient-centred care by taking into account the physical, psychological and social aspects of the patients' orthopaedic complaints, as well as informing and motivating patients for self-management and health promoting activities. The survey was intended to receive feedback on the quality of care from the patients enrolled in this medical specialists' program, particularly concerning the specific aims of the program. A feedback report with individual results and a comparison with the overall results of all participating medical practices was sent out to those practices that provided at least 20 analysable questionnaires. Material and Methods The anonymous survey was conducted using a questionnaire specifically developed for the project. Participating practices handed out questionnaires to up to 100 patients who were enrolled in the program and consulted their orthopaedic or surgical specialist within 3 months of the start of the survey. Completed questionnaires were collected and sent to the research institute for data analysis in a sealed box. Results A total of 10,010 patients from 267 practices took part in the survey. Data analysis (including an anonymous comparison of the results of participating practices) was conducted on the basis of patients' responses from 183 practices that had obtained at least 20 completed questionnaires (8,988 patients, response rate 49.1%). Survey results are presented on doctor-patient communication, scheduling appointments, waiting times, cooperation with general practitioner, referral and treatment. On the whole, patients were satisfied with the care provided by their orthopaedic or surgical specialist. The comparison between the practices revealed significant differences in the patients' sociodemographic features and their feedback on the medical care received. Patients' evaluation of information and the counselling received from their orthopaedic/surgical specialist showed the strongest correlation with overall satisfaction. Referral by their general practitioner had a positive influence on patients' intentions to consult their orthopaedic/surgical specialist again. From the patients' point of view, doctors' information and counselling on self-help activities (e.g. eating habits, physical activity) had the largest potential for improvement. Conclusions The survey's results confirm the objectives of this new orthopaedic health care program, especially motivational counselling on adequate physical activity and self-management. They provide a basis for the further development of the quality of care, in accordance with both the contractual aims and the patients' needs.
Gesehen am 14.09.2018